Similar but different: Revealing the relative roles of species‐traits versus biome properties structuring genetic variation in South American marsh rats - Joyce R. Prado; Alexandre R. Percequillo; Andréa T. Thomaz; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Wetland habitats, and the ecological restrictions imposed by them, structure patterns of genetic variation in constituent taxa. As such, genetic variation may reflect properties of the specific biomes species inhabit, or shared life history traits among species may result in similar genetic structure. We evaluated these hypotheses jointly by quantifying the similarity of genetic structure in three South American marsh rat species ( Holochilus ), and test how genetic variation in each species relates to biome‐specific environmental space and historical stability. Location South America. Taxon Rodentia. Methods Using complementary analyses (Mantel tests, db RDA , Procrustes, covariance structure of allele frequencies and environmental niche models [ ENM s]) with 8,000–32,000 SNP s per species, we quantified the association between genomic variation and geographic and/or environmental differences. Results Significant association between genetic variation and geography was identified for all species. Similarity in the strength of the association suggests connectivity patterns dictated by shared species‐traits predominate at the biome scale. However, substantial amounts of genetic variation are not explained by geography. Focusing on this portion of the variance, we demonstrate a significant quantitative association between genetic variation and the environmental space of a biome, and a qualitative association with varying regional stability. Specifically, historically stable areas estimated from ecological niche models are correlated with local levels of geographic structuring, suggesting that local biome‐specific histories affect population isolation/connectivity. Main conclusions These tests show that although species exhibit similar patterns of genetic variation that are consistent with shared natural histories, irrespective of inhabiting different wetland biomes, local biome‐specific properties (i.e. varying environmental conditions and historical stability) contribute to departures from equilibrium patterns of genetic variation expected by isolation by geographic distance. The reflection of these biome‐specific properties in the genetic structure of the marsh rats provides a window into the differences among South American wetlands with evolutionary consequences for their respective constituent assemblages.